Conserved Cytochrome P450 Evolved in Seed Plants Regulates Flower Maturation - Liu, Zhenhua; Boachon, Benoît; Lugan, Raphaël; Tavares, Raquel; Erhardt, Mathieu; Mutterer, Jérôme; Demais, Valérie; Pateyron, Stéphanie; Brunaud, Véronique; Ohnishi, Toshiyuki; Pencik, Ales; Achard, Patrick; et al. (Molecular Plant, 2015)
Global inspection of plant genomes identifies genes maintained in low copies across taxa and under strong purifying selection, which are likely to have essential functions. Based on this rationale, we investigated the function of the low-duplicated CYP715 cytochrome P450 gene family that appeared early in seed plants and evolved under strong negative selection. Arabidopsis CYP715A 1 showed a restricted tissue-specific expres- sion in the tapetum of flower buds and in the anther filaments upon anthesis, cyp715a1 insertion lines showed a strong defect in petal development, and transient alteration of pollen intine deposition. Comparative expres- sion analysis revealed the downregulated expression of genes involved in pollen development, cell wall biogenesis, hormone homeostasis, and floral sesquiterpene biosynthesis, especially TPS21 and several key genes regulating floral development such as MYB21, MYB24, and MYC2. Accordingly, floral sesquiterpene emission was suppressed in the cyp715a1 mutants. Flower hormone profiling, in addition, indicated a modi- fication of gibberellin homeostasis and a strong disturbance of the turnover of jasmonic acid derivatives. Petal growth was partially restored by the active gibberellin GA3 or the functional analog of jasmonoyl-isoleucine, coronatine. CYP715 appears to function as a key regulator of flower maturation, synchronizing petal expan- sion and volatile emission. It is thus expected to be an important determinant of flower-insect interaction.